The influence of farm input subsidies on the adoption of natural resource management technologies. (27th July 2017) - Koppmair, Stefan; Kassie, Menale; Qaim, Matin
Abstract : Farm input subsidies are often criticised on economic and ecological grounds. The promotion of natural resource management (NRM) technologies is widely seen as more sustainable to increase agricultural productivity and food security. Relatively little is known about how input subsidies affect farmers' decisions to adopt NRM technologies. There are concerns of incompatibility, because NRM technologies are one strategy to reduce the use of external inputs in intensive production systems. However, in smallholder systems of Africa, where the average use of external inputs is low, there may possibly be interesting complementarities. Here, we analyse the situation of Malawi's Farm Input Subsidy Program (FISP). Using panel data from smallholder farm households, we develop a multivariate probit model and examine how FISP participation affects farmers' decisions to adopt various NRM technologies, such as intercropping of maize with legumes, use of organic manure, water conservation practices and vegetative strips. As expected, FISP increases the use of inorganic fertilizer and improved maize seeds. Yet, we also observe a positive association between FISP and the adoption of certain NRM technologies. For other NRM technologies, we find no significant effect. We conclude that input subsidies and the promotion of NRM technologies can be compatible strategies.